The Effects of Flossing Band and Kinesio Taping on Nondominant Knee Joint Muscle Strength, Power and Endurance in Young Adult Males - Il-Seung Seo; Seong-Su Kim; Sang-Wan Han; Youn-Seon Lee; Kyoung-Bin Min (The Asian Journal of Kinesiology)
OBJECTIVES This study investigated the effects of flossing bands and kinesio taping on the muscle function of the non-dominant knee joint, focusing on changes in muscle strength, power, and endurance. METHODS Ten male university students were randomly assigned to three groups: no intervention, kinesio taping, and flossing band application. Participants performed knee flexion, knee extension, and squat exercises, while muscle function in the quadriceps and hamstrings was assessed using an isokinetic dynamometer at angular velocities of 60°/sec (strength), 180°/sec (power), and 240°/sec (endurance). RESULTS The results showed no significant differences in quadriceps strength among the groups(p > 0.05), but hamstring strength improved significantly in the flossing band group compared to the no intervention and kinesio taping groups(p < 0.05). Muscle power in both the quadriceps and hamstrings increased significantly with flossing band application(p < 0.001), while hamstring endurance was significantly enhanced in both the flossing band and kinesio taping groups compared to the no intervention group(p < 0.05). CONCLUSIONS The application of flossing bands significantly enhanced hamstring strength, power, and endurance compared to kinesio taping and no intervention. These findings suggest that flossing bands may be an effective intervention for improving knee joint muscle function, particularly in the non-dominant leg. Further research is needed to explore the long-term effects and practical applications of these interventions in rehabilitation and sports performance.